Cusco: cultural tourism and economic inclusion - Marsano Delgado, José Manuel Enrique (2018)
The study of the satellite accounts of the Cusco region proposes the use of a new methodology to evaluate not only the satellite account of the tourism sector in the region, but also the degree of its economic inclusion, allowing to measure the wealth generated by the sector and the contribution of the workforce to the tourism GDP of the Region. The methodology consists in evaluating the wealth generated and its distribution through the production factors. In this sense, the macroeconomic behavior of the tourism sector in Cusco is evaluated. (Marsano, 2017).